PENGARUH INTELLECTUAL CAPITAL TERHADAP NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL INTERVENING - Hadiwijaya, Rendy Cahyo; Rohman, Abdul (Diponegoro Journal of Accounting, 2013)
The purpose of this studywas todetermine the effect ofintellectual capitaltoward firm valuewiththe financialperformanceas the intervening variable. The independent variable applied in this studywas theintellectual capital which wasmeasured by value added intellectual coefficient (VAICTM). The dependentvariablein this studywas the firm value is measuredbyusing price-to-book value (PBV), whilefinancial performanceas an intervening variable is measured by using return on asset (ROA). The samples of this study were the banking companies listed by the Indonesia Stock Exchange (IDX) within the period of 2007-2011. Data were collected by using purposive sampling method. Based on the mentioned criteria, 22 companies were selected as the population of this study. The data analysis tool used in this study was path analysis with AMOS software 16.0 version.The finding shows that (1) intellectual capital has positive and significant effect to the financial performance. (2) intellectual capital has no effect on firm value. (3) the financial performance has positive and significant effect to mediate the relationship between intellectual capital and firm value.